A HOLISTIC CONCEPT OF NEUROINCOME AS A SOLUTION OF THE â€œTYRANY BOTTOM LINE â€œIN WORKPLACE - Leniwati, Driana; Sukoharsono, Eko Ganis; Prihatiningtias, Yeney Widya; Purwanti, Lilik (The International Journal of Accounting and Business Society, 2020)
PurposeÂ  â€” This research aims to formulate a holistic concept of neuroincome.Design/methodology/approachÂ  â€” The data collected are from various commercial bank employeesâ€™ experience with variation grade and position, local and international bank in Indonesia. Based on a spiritualist paradigm, the data are analysed by intuition using Taubat, Zikir, Doa, and Tafakur (TZDT) method within the framework of Neuro-Psycho Spiritual (NPS) methodology. The NPS methodology is used as an integrated science to study humans holistically by including materialistic, psycho, and spiritual dimensions. Â While the intuition in TZDT frame is a tool utilized to analyze data that relies entirely on God's guidance in the form of intuition and sense.FindingsÂ  â€” The result of the study is a holistic concept of neuroincome in the form of â€œextraâ€ income and physical goods possible converted financially, earned by an individual as his/her working compensation stimulated by companyâ€™s tool/policy/system in workplace such as bonuses financially or bonus in the form of distribution of company shares, incentives, fringe benefits, performances allowances, job allowances, award, facilities and other related financial compensation. The positive stimuli happened if the nerves stimulate the release of hormone to perceive income in positive attitude such as empathy, helpful and sincerity. The negative stimuli happened if the nerves perceive the income excessively so it could make unethical actions or fraud. Then, qonaâ€™ah (sufficient sense) and modesty are found intuitively as a solution of â€œtyranny bottom lineâ€ in workplace. These attitudes stimulate a resurrection of the harmony of materialistic, psycho, and spiritual consciousness to live in a holistic way and bring closer to God in everyday working life.Practical ImplicationsÂ  â€” The holistic concept of neuroincome is explained through Neuro-Psycho Spiritual (NPS) methodology.Originality/valueÂ  â€” Authors are using various commercial bank employeesâ€™ experience with variation grade and position, local and international bank in Indonesia as their subject.Keywords Income, neuroscience, psychology, spirituality, spiritualist paradigm, consciousnessPaper Type Research PaperÂ